Implementasi Sistem Pembelajaran Hybrid Learning sebagai Upaya untuk Meningkatkan Partisipasi Belajar Peserta Didik Tuna Daksa di PKBM Rumpun Aksara Jember - Koten, Elisabeth Ema; Yaum, Lailil Aflahkul; Zusfindhana, Inna Hamida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines the implementation of the Hybrid Learning learning system as an effort to increase the participation of students with physical impairments in PKBM Rumpun Aksara Jember. The aim of this research is to describe how the Hybrid Learning learning system is implemented at PKBM Rumpun Aksara and to determine the supporting factors and inhibiting factors for implementing the Hybrid Learning learning system at PKBM Rumpun Aksara. PKBM Rumpun Aksara is a non-formal educational institution in Indonesia that organizes literacy programs for children and adults who have dropped out of formal education. The problem in this research is the lack of participation level of students with physical impairments to take part in face-to-face learning at PKBM Rumpun Aksara, so a learning innovation is presented that does not require students with physical impairments to always attend PKBM Rumpun Aksara. This learning innovation is Hybrid Learning. Hybrid Learning is a combination of online learning and offline or face-to-face learning. This research uses qualitative relationships with descriptive methods. Data collection techniques were carried out by observation, interviews and documentation. Data analysis techniques used in this research include: data collection, data reduction, data presentation, and drawing conclusions. From the results of this research, it can be concluded that the implementation of the Hybrid Learning system at PKBM Rumpun Aksara starting from the planning stage, the implementation stage to the evaluation stage has been categorized as good, but there are several things that must be considered and adjusted to the needs of students with physical impairments.